(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This petroleum distribution company is located at Quezon City has a total of 198 employees has been operating for 17 years. The company’s policies and procedures may be examined to enhance practices in accordance to the Labor law. The researchers gathered data using open–ended question in interviews with the Human Resource Manager of the company. The researchers were permitted to have the company manual for review and reference. The researchers also used online resources as reference for best practices to compare and contrast with the company’s manual. The researchers identified policies that needed enhancement and development and proposed a No Gift policy and a Data Privacy policy. Also, the researchers propose a Leave for Violence Against Women and Their Children as a component of Compensation and benefits to help women victims, Coaching and mentoring program in staff training and development, enhancement of Transferability of employees, development of an Open Door management style to enable employees to have an opportunity to raise concerns easily to the management. In this study, the researchers proposed policies that is based on current best practices and Labor law that can be implemented or used as reference for an efficient operation concerning its workforce.